2017
DOI: 10.1002/14651858.cd011648.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological interventions for primary biliary cholangitis

Abstract: Based on very low quality evidence, there is currently no evidence that any intervention is beneficial for primary biliary cholangitis. However, the follow-up periods in the trials were short and there is significant uncertainty in this issue. Further well-designed randomised clinical trials are necessary. Future randomised clinical trials ought to be adequately powered; performed in people who are generally seen in the clinic rather than in highly selected participants; employ blinding; avoid post-randomisati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 271 publications
0
12
0
Order By: Relevance
“…Bile acids are known to regulate cholesterol homeostasis and facilitate digestion and absorption of lipids (43). Early studies reported the therapeutic benefits of bile acids in various diseases through the regulation of distinct signaling pathways, including the UPR (43)(44)(45). We previously reported that TUDCA administration in HDM-allergic C57BL/6J mice decreased the UPR, AHR, mucus metaplasia, and airway fibrosis (7).…”
Section: Discussionmentioning
confidence: 99%
“…Bile acids are known to regulate cholesterol homeostasis and facilitate digestion and absorption of lipids (43). Early studies reported the therapeutic benefits of bile acids in various diseases through the regulation of distinct signaling pathways, including the UPR (43)(44)(45). We previously reported that TUDCA administration in HDM-allergic C57BL/6J mice decreased the UPR, AHR, mucus metaplasia, and airway fibrosis (7).…”
Section: Discussionmentioning
confidence: 99%
“…Third, the NNT assumes a causal relationship between UDCA and prolonged LT-free survival. This has long been subject to debate, especially due to Cochrane reporting an absence of treatment benefit 26. As this is a retrospective study in which IPTW was used to adjust for the small differences in baseline characteristics, residual confounding can never be fully ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…This has long been subject to debate, especially due to Cochrane reporting an absence of treatment benefit. 26 As this is a retrospective study in which IPTW was used to adjust for the small differences in baseline characteristics, residual confounding can never be fully ruled out. We are lacking data on the reasons for not treating patients with PBC with UDCA, but especially shortly after its introduction it can be hypothesised that physicians may have been unaware of UDCA or not convinced about its benefits.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17][18][19] As did other more extensive meta-analyses, the Cochrane hepatobiliary group recently concluded once again that there is no demonstrated benefit of UDCA on LT and/or mortality. [17][18][19][20] Such positioning statements, in absence of the results of definitive trials, have fueled the ongoing discussion about the therapeutic potential of UDCA. [21][22][23][24] This might explain the observation in a well-executed national PBC registry that, until recently, as much as 20% of patients remained untreated.…”
Section: Manucript Body Introductionmentioning
confidence: 99%